Mediating role of Emotional Stability and Self-Esteem between Mindfulness and Psychological Wellbeing - ul Ayesha, Taj; Akbar, Waqar; Shaikh, Sadia (International Journal of Psychosocial Rehabilitation, 2020)
Mindfulness and Psychological Wellbeing has received a positive amount of importance in contemporary literature. The present study examines the mediating role of self-esteem and emotional stability on the relationship between Mindfulness and Psychological wellbeing. Respondents’ data on self-esteem and psychological wellbeing was also measured on five-point item scale. Similarly, mindfulness was measured on 15 item scales, whereas emotional stability was measured on ten item personality inventory. 312 salesperson working in retail stores in Pakistan participated in the study by filling the self-administrated questionnaire. Partial least square structural modeling (PLS-SEM) technique was applied to analyze the data. The results of the study reveal self-esteem is a significant mediating variable between Mindfulness and Psychological Wellbeing. However, emotional stability was found statistically insignificant. The results provide the useful insights for policy makers and Organizational behavior practitioners to craft a workplace policy and support the HR Department to design appropriate trainings for the employees. Avenues for Future studies are also suggested.